Soilless crops and farms and the need to protect agricultural land from the perspective of ensuring food security - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2021)
The aim of this paper was to examine whether, despite the increasing use of soilless methods of cultivation and breeding, legal protection of agricultural land is still justified in view of the need to ensure food security. Despite the fact that the use of cultivation and breeding methods that do not require soil has been on the increase, agricultural land remains a basic and indispensable factor of agricultural production. It must be stated that in the current socio-economic situation the new technologies cannot replace traditional agriculture. They may, however, support it by complementing traditional agricultural production, particularly in densely populated areas or in areas where the environmental stress is high. For this reason, legal protection of agricultural land is necessary and fully justified as it ensures agricultural production and, consequently, guarantees food security, also in the ownership aspect as defined in the Act on shaping the agricultural system.